Efektivitas Latihan Peregangan Otot dalam Pengendalian Carpal Tunel Syndrome pada Pekerja Belah dan Sortir Pinang - Budi Aswin; Ismi Nurwaqiah Ibnu; La Ode Reskiaddin (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Carpal Tunnel Syndrome (CTS) is a common musculoskeletal disorder experienced by workers performing repetitive activities, such as those in areca nut splitting and sorting. This study aimed to analyze the effectiveness of muscle stretching exercises in reducing CTS complaints in workers at CV Indokara. A quantitative method with a pre-post design was applied to 44 workers. The intervention involved regular muscle stretching exercises over a period of three weeks. Data analysis included paired t-tests for normally distributed data and Wilcoxon tests for non-normally distributed data, with a significance level set at 95% (p < 0.05). The pre-test results showed a mean CTS complaint score of 2.932 (SD = 0.9999), while the post-test mean was 2.493 (SD = 0.9631). Statistical analysis yielded a p-value of 0.033, indicating a significant reduction in CTS complaints following the intervention. The results revealed improvements in symptoms such as pain, tingling, and numbness in the wrists after the intervention. These findings indicate that muscle stretching exercises effectively alleviate tension and reduce pressure on the median nerve, thereby reducing CTS risk in repetitive tasks. The study recommends incorporating muscle stretching into occupational health programs to minimize CTS in workers performing repetitive movements